Increased Production of the Value-Added Biopolymers Poly(R-3-Hydroxyalkanoate) and Poly(γ-Glutamic Acid) From Hydrolyzed Paper Recycling Waste Fines - Scheel, Ryan A.; Fusi, Alexander D.; Min, Byeong C.; Thomas, Christopher M.; Ramarao, Bandaru V.; Nomura, Christopher T. (Frontiers in Bioengineering and Biotechnology, 2019)
Reject fines, a waste stream of short lignocellulosic fibers produced from paper linerboard recycling, are a cellulose-rich paper mill byproduct that can be hydrolyzed enzymatically into fermentable sugars. In this study, the use of hydrolyzed reject fines as a carbon source for bacterial biosynthesis of poly(R-3-hydroxyalkanoate) (PHA) and poly(γ-glutamic acid) (PGA) was investigated. Recombinant Escherichia coli harboring PHA biosynthesis genes were cultivated with purified sugars or crude hydrolysate to produce both poly(R-3-hydroxybutyrate) (PHB) homopolymer and medium chain length-containing copolymer (PHB-co-MCL). Wild-type Bacillus licheniformis WX-02 were cultivated with crude hydrolysate to produce PGA. Both PHB and short chain-length-co-medium chain-length (SCL-co-MCL) PHA yields from crude hydrolysate were a 2-fold improvement over purified sugars, and the MCL monomer fraction was decreased slightly in copolymers produced from crude hydrolysate. PGA yield from crude hydrolysate was similarly increased 2-fold. The results suggest that sugars from hydrolyzed reject fines are a viable carbon source for PHA and PGA biosynthesis. The use of crude hydrolysate is not only possible but beneficial for biopolymer production, eliminating the need for costly separation and purification techniques. This study demonstrates the potential to divert a lignocellulosic waste stream into valuable biomaterials, mitigating the environmental impacts of solid waste disposal.